Peran Sistem Kriptografi Sebagai Fondasi Keamanan Informasi Dan Privasi Data Pribadi - M. Rizky Ramadhan; M. Fadillah Arief; M. Afriza Miftahul Huda; Indra Gunawan (Universitas Labuhanbatu, 2026)
The rapid development of digital technology has made the online exchange of personal data increasingly widespread, but on the other hand, it increases the risk of information leaks and misuse. Cases of personal data breaches in Indonesia demonstrate that weak security systems remain a potential avenue for cybercrime. One key solution to address this problem is the implementation of cryptographic systems. This study aims to analyze the role of cryptographic systems in maintaining the confidentiality, integrity, and authenticity of personal data as a foundation for information security in the digital era. The research method used is descriptive analysis, using a literature review approach of various scientific sources from 2021–2025. The results show that the application of cryptographic algorithms such as AES, RSA, and hybrid cryptography systems has proven effective in protecting data from unauthorized access and manipulation. Furthermore, the integration of cryptography with artificial intelligence and post-quantum cryptography technologies is a crucial innovation for strengthening information security systems in the future. This study concludes that cryptography is a fundamental element in personal data protection and is key to building a robust, efficient, and sustainable information security system amidst the increasing threat of global cybercrime.